'Over There, in the Future': The Transformative Agency of Place‐Based Design Education in Remote Aboriginal Communities. (25th November 2018) - Edwards‐Vandenhoek, Samantha
Abstract: This article outlines the learning design, implementation and shared outcomes of an intensive placed‐based design education programme that was delivered in a specific remote high school learning context in the Warmun Aboriginal community, East Kimberley, Western Australia. Place‐based design education seeks to assist vulnerable young people in shaping their own environments and futures. A two‐way learning framework that emphasised self‐actualisation, co‐creation and shared insights and involved learning through story‐sharing and connecting content to place was adopted. This article suggests that providing students with opportunities to share and acquire Indigenous design knowledge developed their visual thinking, digital literacy, problem‐solving and entrepreneurial skills. Such knowledge, experience and skills build confidence and improve educational outcomes, and will directly benefit Indigenous communities in the long term.